College Ranking Analysis Using VIKOR Method - Adidtya Perdana; Arief Budiman (Journal of Computer Networks, Architecture and High Performance Computing, 2021)
College ranking is the main thing used as a basis to attract prospective new students. Prospective new students will generally look for related information from which universities are the best to choose in the future. In the ranking of universities based on the official page of the Ministry of Research, Technology and Higher Education, the ranking of universities, both public and private, can be a reference for recruiting prospective students. The better the college ranking, the more attractive prospective new students are. To determine the ranking of a university, a decision support system is needed. There are many methods available from the decision support system, but in this study, the author will use the VIKOR method (Visekriterijumsko Kompromisno Rangiranje), which is part of the MCDM (Multi-Criteria Decision Making), as a solution to these problems. The VIKOR method is a multi-criteria optimization method that can be used on fairly complex systems. In this study, the sample data used came from 10 universities in the city of Medan, where the initials of each naming were colleges A to J. From the results of research analysis using the VIKOR method, the ranking results were as follows, where college B got the first rank with the lowest score of 0. Then the second rank was college G and in the third rank was college H with each score of 0.248211396 and 0.304702661. For the fourth, fifth, sixth, seventh to tenth ranks, they are sorted from colleges A, I, C, E, F, D, and J.